The Effect of Single and Multiple Layers of Thin Aluminum Cylinder Walls on High-Speed Impact Behavior - Witono Hardi,; Amat Umron,; Mohammad Shalahuddin Abdul Aziz, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The use of thin-walled structures as impact energy-absorbing media has been carried out by many researchers. The cylindrical tube shape is very popular and is used in an extensive area. Many ways are done to increase the ability to absorb energy and reduce the maximum reaction force. This study investigates the behavior of single- and multiple-layer thin aluminum tubes. The finite element method is used to model specimens and impactors. One end of the sample is subjected to a fixed support, and the other is subjected to impact at a speed of 50 m/s. The specimens used consisted of one, two, three, and four layers with a fixed total thickness of 4 mm. The results showed that the single layer has the slightest total deformation and the most significant reaction force for relatively the same energy absorption. Using more layers increases the deformation length but decreases the reaction force. This is due to the absence of adhesive between layers, so all layers work together simultaneously. The results of this study assist as a recommendation for the manufacture of high-speed impact energy-absorbing structures.